Ketupat Tradition in Sustainable Development Goals (SDGs) : Local Wisdom for Improvement of Infant’s and Maternal Health Quality on Mataraman Javanese Peoples at Surabaya - FX. Sri Sadewo; Martinus Legowo; Refti Handini Listyani; Diyah Utami (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
Rituals about death can be seen as a family's willingness to lose a member, but also as an attempt to provide confidence in the transition from the world of the living to the world of the dead. These rituals are often only carried out at certain times and become important for adults. Meanwhile, the death of a child under five, especially when a miscarriage occurs, is often not remembered. In fact, this is not entirely true for the Javanese Mataraman community. Through this research, the presence of children under five and/or fetuses in the womb that died has taken an important position in the kupatan tradition. These memories should be suspected of helping to minimize infant deaths and miscarriages. This can be known by using a qualitative approach with a phenomenological perspective of E. Husserl on the Kupatan tradition of Javanese society. This tradition is not only carried out in rural areas, but in urban areas. Through the illness narrative, the Kupatan tradition has socialized the importance of care during pregnancy. In the kupatan tradition, narratives of success and failure in pregnancy care are well recorded. From the narrative of failure, a mother and her husband develop a business for their success.